Effect of Planting Portulaca oleracea L. on Improvement of Salt-Affected Soils - Jing Dong; Jincheng Xing; Tingting He; Sunan He; Chong Liu; Xiaomei Zhu; Guoli Sun; Kai Wang; Lizhou Hong; Zhenhua Zhang (Applied Sciences)
Saline–alkali land is a critical factor limiting agricultural production and ecological restoration. Utilizing salt-tolerant plants for bioremediation represents an environmentally friendly and sustainable approach to soil management. This study employed the highly salt-tolerant crop Portulaca oleracea L. cv. “Su Ma Chi Xian 3” as the test material. A plot experiment was established in coastal saline soils with planting P. a- oleracea (P) and no planting (CK) under three blocks with the different salt levels (S1: 2.16 g/kg; S2: 4.08 g/kg; S3: 5.43 g/kg) to systematically evaluate its salt accumulation capacity and effects on soil physicochemical properties. The results demonstrated that P. oleracea exhibited adaptability across all three salinity levels, with aboveground biomass following the trend PS2 > PS3 > PS1. The ash salt contents removed through harvesting were 1.29, 2.03, and 1.74 t/ha, respectively, in PS1, PS2, and PS3. Compared to no planting, a significant reduction in bulk density was observed in the 0–10 and 10–20 cm soil layers (p < 0.05). A significant increase in porosity by 9.72%, 16.29%, and 12.61% was found under PS1, PS2, and PS3, respectively, in the 0–10 cm soil layer. Soil salinity decreased by 34.20%, 50.23%, and 48.26%, in the 0–10 cm soil layer and by 14.43%, 32.30%, and 26.42% in the 10–20 cm soil layer under PS1, PS2, and PS3, respectively. The pH exhibited a significant reduction under the planting treatment in the 0–10 cm layer. A significant increase in organic matter content by 13.70%, 12.44%, and 13.55%, under PS1, PS2, and PS3, respectively, was observed in the 0–10 cm soil layer. The activities of invertase and urease were significantly enhanced in the 0–10 and 10–20 cm soil layers, and the activity of alkaline phosphatase also exhibited a significant increase in the 0–10 cm layer under the planting treatment. This study indicated that cultivating P. oleracea could effectively facilitate the improvement of coastal saline soils by optimizing soil structure, reducing salinity, increasing organic matter, and activating the soil enzyme system, thereby providing theoretical and technical foundations for ecological restoration and sustainable agricultural utilization of saline–alkali lands.